Immunomodulatory properties of Leishmania tarentolae extracellular vesicles containing the Spike protein of SARS-CoV-2 - Medina, Ana Catalina; Acevedo Ospina, Hamlet; Descoteaux, Albert (Frontiers in Parasitology, 2024)
Extracellular vesicles released by the protozoan parasite Leishmania display immunomodulatory properties towards mammalian immune cells. In this study, we have evaluated the potential of extracellular vesicles derived from the non-pathogenic protozoan Leishmania tarentolae towards the development of a vaccine adjuvant. As a proof-of-concept, we expressed in L. tarentolae a codonoptimized SARS-CoV-2 Spike protein fused to the L. mexicana secreted acid phosphatase signal peptide in N-terminal and to a 6X-His stretch in C-terminal. Extracellular vesicles released by the engineered L. tarentolae were isolated by ultracentrifugation and Fast Protein Liquid Chromatography and were characterized via Nano Tracking Analysis, and transmission electron microscopy. The recombinant S protein was present in extracellular vesicles released by L. tarentolae, as determined by Western blot analyses and immuno-electron microscopy. Next, we evaluated the immunomodulatory potential of extracellular vesicles containing the S protein towards bone marrow-derived macrophages and bone marrow-derived dendritic cells. Our data show that in bone marrow-derived dendritic cells, extracellular vesicles containing the S protein induced an increased expression of proinflammatory genes compared to plain extracellular vesicles whereas the opposite was observed in bone marrowderived macrophages. These findings reveal the immunomodulatory potential of L. tarentolae extracellular vesicles and provide a proof-of-concept that they can be used as adjuvant in the context of dendritic cell stimulation.